Ethnographic research: proposal to develop research competence in university students - Quispe-Morales, Rolando Alfredo (2022)
The research was developed in order to verify the influence of the application of the ethnographic research proposal in the development of research competence in university students. Investigation of mixed type and sequential explanatory design (DEXPLIS). The population consisted of 38 students and the sample of 15 students. The estimation scale and the group interview guide were used as instruments. The hypothesis test was performed using the Wilcoxon statistician. It is concluded that the application of the ethnographic research proposal significantly influences the development of research competence in university students.